The Learning Pattern of Postgraduate Students: A Case Study of Some Postgraduate Program Students of Yogyakarta State University - D N Yusuf; Nasiwan (PT FORMOSA CENDEKIA GLOBAL, 2023)
The objective of this study is to obtain a descriptive description of learning patterns and the driving and inhibiting factors of learning for postgraduate students at Yogyakarta State University (YSU). This study used a qualitative method. The subjects in this study were selected using purposive sampling technique. Data collection was administered through in-depth interview and observation techniques. Data analysis was conducted through data reduction, data display, and conclusions. The research findings show the following results. First, YSU postgraduate students do not have a fixed or steady frequency, duration and place of study every day. Second, YSU postgraduate students tend to have the characteristics of learning independently but individually. This condition can be formed because it is influenced by internal factors such as the subjective view of students who have their respective views on how to learn effectively and efficiently, and external factors such as the academic atmosphere and learning facilities on campus. Third, for YSU postgraduate students, the motivational aspects of learning and the conditions of the campus environment can hinder and encourage their learning activities